Applying Health Behaviour Frameworks to Cities’ Climate Strategies Promoting Sustainable Transport and Mobility (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Cities have a crucial role in promoting health and climate neutrality through sustainable transport and mobility. Behavioural frameworks may improve the effectiveness of promotion. This study applied the elements of two well-recognised frameworks – Behaviour Change Wheel (BCW) and Socioecological model (SEM) – to the Climate City Contracts (CCCs) and Sustainable Urban Mobility Plans (SUMPs) of the six Finnish EU Mission Cities. The study was a part of a larger investigation aiming to strengthen the transformative capacity of the cities to promote climate neutrality and public health through sustainable transport and mobility.Methods: The data included the sustainable transport and mobility actions presented in the CCCs and SUMPs of the cities. First, the actions were mapped into the elements of BCW. Second, the same actions were mapped against the multiple levels of SEM. Third, the actions in the SUMPs were analysed.Results: Altogether, 51 individual actions were discovered in the CCCs. Forty (78%) actions were mappable to BCW. Most actions targeted psychological capabilities and physical opportunities. The actions appeared quite vague for the practical implementation, and their variability seemed quite narrow considering the size and heterogeneity of the population.Forty-seven (92%) actions in CCCs were mappable against SEM. The actions focused mainly on policy level. Some community level and institutional actions were also discovered. Very few or no actions were planned at the individual or interpersonal level.The actions in SUMPs were much more detailed and pragmatic than in CCCs. Also, the number of actions was far greater and in most cities the actions were listed under specific developmental themes and/or goals. Due to the differences in presenting the actions and the high number of actions, mapping against BCW or SEM was not applicable.Conclusion: Behavioural frameworks were scarcely utilised in the CCCs. The SUMPs seemed more promising, but their diversity prevented from making behavioural conclusions about the actions. To summarise, there is much unused potential to include health behaviour frameworks in the promotion of sustainable transport and mobility to achieve better accessibility, feasibility, and effectiveness.Support/Funding Source: The Ministry of Economic Affairs and Employment of Finland